A Desulfonylative Approach in Oxidative Gold Catalysis: Regiospecific Access to Donor‐Substituted Acyl Gold Carbenes. Issue 40 (12th August 2015) - Chen, Hongyi; Zhang, Liming
Abstract Donor‐substituted acyl gold carbenes are challenging to access selectively by gold‐promoted intermolecular oxidation of internal alkynes as the opposite regioisomers frequently predominate. By using alkynyl sulfones or sulfonates as substrates, the oxidative gold catalysis in the presence of substituted pyridine N‐oxides offers regiospecific access to acyl/aryl, acyl/alkenyl, and acyl/alkoxy gold carbenes by in situ expulsion of sulfur dioxide. The intermediacies of these reactive species are established by their reactivities, including undergoing further oxidation by the same oxidant, cyclopropanation of styrenes, engaging in a [3+2] cycloaddition with α‐methylstyrene, and conversion into dienones.